The musical practice of the Sandomierz Benedictine nuns during the eighteenth century - Walter-Mazur, Magdalena (Interdisciplinary Studies in Musicology, 2018)
The congregation of the Benedictine nuns of Sandomierz, active between 1615 and 1903, belonged to wealthy magnatial foundations, which allowed the convent to foster cultural activities. Special emphasis was placed on musical performance of various types - the musical adornment of the liturgy. The ‘Glory of God’, as Benedictine nuns referred to it, constituted the essence of their congregational life. On weekdays, the celebration of the Liturgy of the Hours, Masses and - occasionally - other services in choir took six hours, and on numerous feast days of the liturgical year, when the Liturgy of the Hours was sung, not read, it required even more time. The higher the rank of the feast day, the greater was the effort to stress its importance by providing it with a proper musical setting, which led to the cultivation of musical practices of various kinds on special occasions. The musical repertory of the Sandomierz Benedictine nuns comprised plainchant without instrumental accompaniment, plainchant with organ accompaniment, polyphonic a cappella singing (referred to as ‘figure’), vocal instrumental music (‘fractus’) and instrumental music. A picture of religious musical practice emerges primarily from extant musical sources, and also from a ‘choir agenda’ from 1749, a convent chronicle of the years 1762-1780, ‘treasury records’ from 1739-1806 and convent registers. Eighteenth-century sources document the musical activity of twenty-four nuns of the Sandomierz convent, some of them considered to be ‘professional’ musicians and referred to as ‘singers and players’. The most interesting, but also most problematic, areas are vocal instrumental practice and the likely consitution of the nuns’ music chapel. We find information about nuns playing keyboard instruments, violin, viola da gamba, tromba marina and horn.